Discuss on scientific construction of ecological risk assessment methods in the high background areas of soil heavy metals - ZHANG Fugui; CHENG Xiaomeng; MA Honghong; SUN Binbin; PENG Min (浙江大学学报. 农业与生命科学版)
In order to scientifically identify and evaluate the soil heavy metal pollution and ecological risk in the background area with high heavy metal contents, 309 sets of maize and rhizosphere soil samples were collected in Hezhen Town of Hezhang County of Guizhou Province, and 20 maize samples from different parts of roots, stems and leaves were collected. The contents of heavy metals (As, Cd, Cr, Cu, Hg, Ni, Pb, and Zn) were analyzed in topsoil and maize samples. Also, speciations of heavy metals in the rhizosphere soil samples were analyzed (Cr was not measured). The results showed that the contents of heavy metals in the soils were relatively high, and the averages were remarkably higher than the national soil background value (NBV), and the content of Cd element was nearly seven times higher than the NBV. The soil was mainly acidic, and the ecological risk was high based on the total amount of heavy metals. Speciation analysis indicated that heavy metals (As, Cu, Hg, Ni, Pb, and Zn) mainly existed in the forms of strong organic binding state and residual state, with low bioavailability, and the bioavailability of Cd was high. The ecological risk was mainly caused by Cd based on speciation of heavy metals. In the soil-corn system, the bioconcentration factors and translocation factors were both low, so heavy metals were difficult to be enriched in the corn. The contents of heavy metals in corn seeds did not exceed the standard, and the crops were safe. The above results provide a theoretical basis for further studying the migration and transformation law of heavy metals in rock-soil-gas-biota media, integrating geology, pedology and biology to establish a unified standard, and scientifically evaluating the ecological environment risk and health risk.